2022
DOI: 10.3389/fmicb.2022.1030523
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional differences between major Fusarium pathogens of maize, Fusarium verticillioides and Fusarium graminearum with different optimum growth temperatures

Abstract: Fusarium verticillioides and Fusarium graminearum are important pathogens causing disease in maize (Zea mays) worldwide. The distributions of these fungal pathogens vary greatly in different regions and in different years, and are influenced by environmental and climatic conditions. Temperature has significant effects on the growth and mycotoxin production of Fusarium species. In this study, the effects of temperature on the growth and pathogenicity of F. verticillioides and F. graminearum were investigated. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Temperatures ranging from 25 to 30 °C are considered to be suitable for growth. 42 We chose the most reported temperatures of 25 and 30 °C for study, and the results are shown in Figure 1 and Table 1 Major triazole chiral fungicides, including prothioconazole, cyproconazole, propiconazole, and bitertanol, have large differences in stereoselective activity against target pathogens. Mefentrifluconazole also exhibited differences in the stereoselective activity against some target pathogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperatures ranging from 25 to 30 °C are considered to be suitable for growth. 42 We chose the most reported temperatures of 25 and 30 °C for study, and the results are shown in Figure 1 and Table 1 Major triazole chiral fungicides, including prothioconazole, cyproconazole, propiconazole, and bitertanol, have large differences in stereoselective activity against target pathogens. Mefentrifluconazole also exhibited differences in the stereoselective activity against some target pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…verticillioides varied under different environmental conditions. Temperatures ranging from 25 to 30 °C are considered to be suitable for growth . We chose the most reported temperatures of 25 and 30 °C for study, and the results are shown in Figure and Table .…”
Section: Results and Discussionmentioning
confidence: 99%